Neck phlegmon in COVID-19 patients - Trybek, Arkadiusz; Lichota, Piotr; Wilczynski, Jacek; Zieliński, Rafał (Medical Studies/Studia Medyczne, 2021)
Reports on patients hospitalised due to inflammatory diseases of the soft tissues in the head suggest worsening of the course of the underlying disease in the case of coexisting infection with the SARS-CoV-2 virus. The cases of 2 patients with neck phlegmon in the course of Coronavirus disease 19 (COVID-19) hospitalised at our Otorhinolaryngological Unit have been presented in the paper. Despite intensive treatment, the disease was fatal in both cases. COVID-19 probably has a significant impact on the course of disease and treatment results in the cases of patients with neck phlegmon. Coexisting diseases may seriously worsen the prognosis in patients with neck phlegmon and COVID-19. Further research is required to explain the mechanism of the impact of SARS-CoV-2 infection on the course of phlegmon in the head and neck region.